Epilepsy and Autism Spectrum Disorder: An Epidemiological Study in Shanghai, China - Zhang, Anyi; Li, Jijun; Zhang, Yiwen; Jin, Xingming; Ma, Jun (Frontiers in Psychiatry, 2019)
Autism spectrum disorder (ASD) is a neurodevelopmental disease that may involve various brain abnormalities. However, there are few large epidemiological studies on the relation between epilepsy and ASD in terms of different gender and age. This study aimed to evaluate the relation between epilepsy and ASD based on 74,251 Chinese children aged 3-12 years who were recruited from kindergartens and primary schools in China. ASD was diagnosed according to the DSM-V, and verification of epilepsy was based on medical records. The enrolled children diagnosed with ASD were examined by MRI and took genetic tests to rule out other neurological and congenital diseases. The raw odds ratio (OR) was 60.53 (95% CI = 37.80-96.92, P<0.01) for epilepsy and ASD, and the adjusted OR was 38.99 (95% CI = 20.70-73.41, P<0.01) after controlling the confounders. Moreover, the adjusted OR was significantly higher in girls (OR = 45.26, 95% CI = 16.42-124.76, P<0.01) than in boys (OR = 32.64, 95% CI = 14.33-74.34, P<0.01). Among children with younger age, the adjusted OR was the highest (OR = 75.12, 95%CI = 22.80-247.48.16, P<0.01). These findings suggested that epilepsy might be closely linked to the development of ASD, especially for the early onset epilepsy and among girls.